Perceptions of barriers to providing good cat care in Malaysian clinical practices - Zaini, Syamira Syazuana; Phillips, Claire; MacKay, Jill R.D.; Langford, Fritha (Cambridge University Press, 2023)
Many veterinary practices around the world do not meet basic post-operative cat care, thereby compromising cat welfare. Understanding why the appropriate care is not always given is important. The current study used a mixed methods approach of two phases, to investigate the barriers Malaysian veterinarians face in seeking to provide good cat care in practice. Phase 1 involved a survey consisting of 14 questions which were divided into three sections (demographic details, basic management and barriers experienced by practices) and emailed to 143 Malaysian veterinarians. While for phase 2, 20 interviews were undertaken (recruited from the survey sample) to further elaborate on the results. A Thematic Analysis was conducted to extract the main barriers experienced by participants. A total of 49 veterinarians completed the survey. Over half of the respondents were senior veterinarians (i.e. those with two or more years in practice) (53.1%; n = 26) who were aware of the basic environmental provisions that cats need post-surgery such as bedding and toileting facilities (57.1%; n = 28). Cost (47%; n = 23) was the biggest restriction to good care provision. Interview findings showed that participants were aware of comfortable post-surgery environments helping recovery, but barriers were highlighted: workload factors and a lack of understanding of cat pain behaviours and associated stress. This suggested that participants had the knowledge required to provide good cat care but experienced difficulties putting this into practice. Therefore, to improve cat welfare in veterinary practice, instead of focusing purely on education, interventions to increase good cat care could include targeted elements that support behaviour change to overcome the barriers.